A high-spin diradical dianion and its bridged chemically switchable single-molecule magnet. Issue 29 (30th June 2021) - Cui, Haiyan; Hu, Zhao-Bo; Chen, Chao; Ruan, Huapeng; Fang, Yong; Zhang, Li; Zhao, Yue; Tan, Gengwen; Song, You; Wang, Xinping
Abstract : We report a triplet diradical dianion in magnesium complex with Δ E ST = 0.94 kcal mol −1 (473 K). Its iron analog is the first single-molecule magnet bridged by a diradical dianion, and the SMM property is switched off through two-electron reduction. Abstract : Triplet diradicals have attracted tremendous attention due to their promising application in organic spintronics, organic magnets and spin filters. However, very few examples of triplet diradicals with singlet–triplet energy gaps (Δ E ST ) over 0.59 kcal mol −1 (298 K) have been reported to date. In this work, we first proved that the dianion of 2, 7-di- tert -butyl-pyrene-4, 5, 9, 10-tetraone (2, 7- t Bu2 -PTO) was a triplet ground state diradical in the magnesium complex 1 with a singlet–triplet energy gap Δ E ST = 0.94 kcal mol −1 (473 K). This is a rare example of stable diradicals with singlet–triplet energy gaps exceeding the thermal energy at room temperature (298 K). Moreover, the iron analog 2 containing the 2, 7- t Bu2 -PTO diradical dianion was isolated, which was the first single-molecule magnet bridged by a diradical dianion. When 2 was doubly reduced to the dianion salt 2K2, single-molecule magnetism was switched off, highlighting the importance of diradicals in single-molecule magnetism.